Documentación II. Palestine - Destruction of health infrastructure in Gaza - Israel´s genocide against Palestinians - UNITED NATIONS HUMAN RIGHTS COUNCIL,; AMNESTY INTERNATIONAL, (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2025)
Documentation included in this section DOCUMENTO 1. United Nations Human Rights Council Thematic Report: ‘Attacks on hospitals during the escalation of hostilities in Gaza (7 October 2023 – 30 June 2024)’, 31 December 2024. DOCUMENTO 2. Amnesty International Report: Israel’s Genocide Against Palestinians in Gaza (‘You Feel Like You Are Subhuman’) – Conclusion and Recommendations, 5 December 2024.